PENGGUNAAN MEDIA PROMOSI KESEHATAN KARTU KUARTET TERHADAP PERILAKU HIDUP BERSIH DAN SEHAT PADA SISWA SD DI KECAMATAN DEPOK SLEMAN - , DIAN KUSUMAWATI, Ema Madyaningrum, S.Kep., Ns., M.Kes ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Development and construction of clean and healthy behaviors in children of primary school age is a way to improves the quality of human as early as possible, so that a healthy lifestyle formed. Applied behavior early believed to have a positive impact for the generation, one of them to create the environments, circumstances, and fun activities so can increase the degree of health for children in elementary school. Objective: To determine the effect of the utilization of health promotion media quartet card towards the clean and healthy behaviors in elementary school students in the sub-district Depok Sleman. Method:This research used quasi experimental design with pretest-posttest with control group design. The subject of study a total of 101 students in class VI, which is divided into 53 students to the intervention group and 48 students for the control group that determined by purposive technique simple random sampling in November 2012-January 2013. Data is collected by observation sheets and analyzed using statistic t-test. Result: The results of the study showed the significant differences between pretest-posttest value clean and healthy behaviors in the treatment group with the mean increase 32,5Â±0,41